Industrial Mining Policy, Innovation, and Firm Business Performance in Indonesia: A Literature Review - Jayana, Agus; Nurul Fadly Bin Habidin; Zuraidah Binti Zainol; Hidayat, Rizky (Journal of Trends Economics and Accounting Research, 2023)
This study uses a qualitative approach in the form of a literature review to explore existing scholarly sources, identifying the most important themes and points of view related to mining policy, innovation and firm performance in Indonesia. The study aims to identify how these factors contribute to sustainable development, improve mining operations, and enhance overall company performance. Existing scholarly sources form the basis of the analysis, which identifies key themes and insights. The results reveal the prominent role of innovation as a mediating link between policy and firm business performance. It is because innovation can help create new methods and technical developments that fill the gap between policy stipulations for mining companies’ success. However, more empirical verification is needed to support these findings. From a practical point of view, companies in the mining sector should target process and product innovation to achieve sustainable competitive advantage. Highlighting technological advancements and environmentally friendly ways of operation can improve operating efficiency and reduce environmental impact while helping one survive in a competitive international market. In sum, this model gives an encompassing view of the link between mining policy, innovation, and company performance; it shows that regulation is a factor in promoting sustainable development.